Landscape as a tourism resource in Protected Natural Areas: Case study Rancheria Chilapa 2da.Seccion (Cañaveralito), Centla, Tabasco - Martínez-Rodríguez, Angel Adiel; Juárez-López, José Francisco; Ortiz-Salaz, Leticia; Galmiche-Tejeda, Ángel (Ecosistemas y Recursos Agropecuarios, 2021)
The potential for tourism in Rancheria Chilapa 2da Section, which is located in the Pantanos de Centla Biosphere Reserve (RBPC) was evaluated. Landscape Unit (UP) evaluation, through both, direct-mixed and indirect (BML) methods were used. Results were used to carry out an evaluation of the potential for tourism by a panel composed of inhabitants of the community, general public and landscape experts. Also, an inventory of natural and cultural tourist resources was carried out. The type of use of each natural resource and the tourist potential were determined by the panel’s preferences. Landscape units, natural resources, cultural and tourist activities were marked on community maps. Five landscape units were established; the most important landscape units were the lagoon ecosystem (UPN1), the scrubs (UPN4) and low sub-perennial forest (UPN1), with respective values of landscape visual quality of 21.40, 19.40 and 19.13. Categories fluctuated between unique and stimulating. Classes A, B and C were determined by BML method. UPN1 was category of area of high quality, UPN4, UPN 5 and UPN2 were medium and UPN3 was low. Eight tourist activities were identified (six of ecotourism and two of adventure tourism). According to the panel, the landscape value of the area studied was 18.09 with a category of preserved for ecotourism and adventure tourism. This indicates that the village has tourism potential as an alternative for its socio-economic development.